Oogenesis pattern and type of ovariole of the parasitoid Palmistichus elaeisis (Hymenoptera: Eulophidae) - Andrade, Gilberto S.; Sousa, Adalberto H.; Santos, Juliana C.; Gama, Farah C.; Serrão, José E.; Zanuncio, José C. (Anais da Academia Brasileira de Ciências, 2012)
The knowledge on ovigeny in parasitoids is important for basic studies on physiology and applied biological control. The ovigeny pattern and type of ovariole of the parasitoid Palmistichus elaeisis Delvare & LaSalle (Hymenoptera: Eulophidae) were studied in newly-emerged females at seven, 14, 24 and 48 h intervals after their emergence from Tenebrio molitor L. pupae (Coleoptera: Tenebrionidae). Females of P. elaeisis presented ovaries composed by four ovarioles of the meroistic polytrophic type. The yolk accumulation and chorionogenesis in P. elaeisis were concluded 24 h after the female emergence. The 48 h-old females show a high quantity of egg ready for oviposition. These findings can help to improve the mass production of P. elaeisis and the augmentative biological control by using this natural enemy.
Keywords: Biological control; Morphology; Natural enemies; Ovigeny